2020
DOI: 10.2147/cmar.s251271
|View full text |Cite
|
Sign up to set email alerts
|

<p>Clinical Significance of Red Cell Distribution Width and Circulating Tumor Cells with an Epithelial–Mesenchymal Transition Phenotype in Lung Adenocarcinoma</p>

Abstract: To determine the prognostic value of red cell distribution width (RDW) and circulating tumor cells with epithelial-mesenchymal transition phenotype (M-CTC) in lung adenocarcinoma (LUAD). Patients and Methods: Clinical and laboratory data of 60 patients with LUAD were collected. CTCs were isolated from their peripheral blood using the CanPatrol TM CTC enrichment method. The indicators of RDW and neutrophil lymphocyte ratio (NLR) were calculated based on the laboratory standards. Results: A total of 60 LUAD pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 44 publications
0
19
0
Order By: Relevance
“…RNA-ISH was used to detect CTCs through the following target sequences: CD45 (leukocyte biomarker); vimentin and Twist (mesenchymal biomarkers); EpCAM and CK8/18/19 (epithelial biomarkers) 8 , 29 , 30 (Fig. 6 ).…”
Section: Methodsmentioning
confidence: 99%
“…RNA-ISH was used to detect CTCs through the following target sequences: CD45 (leukocyte biomarker); vimentin and Twist (mesenchymal biomarkers); EpCAM and CK8/18/19 (epithelial biomarkers) 8 , 29 , 30 (Fig. 6 ).…”
Section: Methodsmentioning
confidence: 99%
“…Many studies have shown that the EMT phenotype can be related to distinct clinical characteristics of the tumor, such as proliferation status, clinical stage, etc. In a study by Peng et al (2020) [ 53 ], CTCs from 84 patients were analyzed. The average positive rate of CTCs was 96% (median 5; range 0–68).…”
Section: Clinical Relevance Of Emt and Csc Phenotypes In Nsclc Patientsmentioning
confidence: 99%
“…The average positive rate of CTCs was 96% (median 5; range 0–68). EMT + CTCs were detected in 73% of patients [ 53 ]. Increased EMT + CTCs significantly correlated with lymphatic metastasis, tumor stage, and Ki67 overexpression.…”
Section: Clinical Relevance Of Emt and Csc Phenotypes In Nsclc Patientsmentioning
confidence: 99%
“…Although, in recent years, surgery, radiotherapy, chemotherapy and molecular targeted therapy have greatly improved the treatment of lung cancer, the 5-year overall survival rate is still low, so lung cancer is a major disease threatening people's health. [ 2 , 3 ]…”
Section: Introductionmentioning
confidence: 99%
“…Invasion and metastasis of lung cancer is the main reason that affects the quality of patients life, thus leading to poor therapeutic effect. [ 2 ] The lack of sensitive and effective methods for the detection of early invasion and metastasis of lung cancer is the main reason for the failure of detecting early lung cancer and intervention, and it is also an important factor for the increase of mortality. [ 4 ]…”
Section: Introductionmentioning
confidence: 99%